Advertising and service quality in the mobile phone industry in Kenya - Gakii, Annstellah; Murigi, Elishiba M. (My University, 2019)
Purpose: The purpose of the study is to determining the effect of integrated marketing communication on service quality in the Mobile Phone Industry in Kenya. Methodology: The methodology employed a descriptive research design. This study focused on 1050 staffs from the marketing, ICT and customer service departments of the four mobile phone network providers in Kenya. The study used stratified sampling method. The target population has1050 staffs, therefore by use of Krejcie and Morgan’s method of determination of a sample size the eventual sample size obtained was composed of 278 respondents. Primary data was collected by means of a semi-structured questionnaire. Test-retest technique of reliability testing was employed. The data collected was analysed using descriptive statistics (measures of central tendency, regression and measures of variations) with the help of Statistical Package for Social Sciences (SPSS) version 20 to achieve the objectives of the study. The findings were presented using tables, frequencies and percentages. Findings: The study found out that the calculated value was greater than the critical value (4.561> 2.83) an indication that advertising, sales promotion, publicity and public relations all have a significant effect on service quality. The significance value was less than 0.05 indicating that the model was significant. Unique contribution to theory, practice and policy: The study recommended that future studies should consider replication using different approach so as to incorporate other aspects of advertising and service quality other than ones in the study.
Keywords: Service Quality; Integrated Marketing Communication; Advertising; Communication; Perceived Service; Expected Service; Service Performance.